2005
DOI: 10.1128/aac.49.1.276-280.2005
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Profile of Ertapenem against Klebsiella pneumoniae and Escherichia coli in a Murine Thigh Model

Abstract: The pharmacodynamic profile of ertapenem was evaluated in a neutropenic mouse thigh infection model. Extended-spectrum beta-lactamase (ESBL)-positive and ESBL-negative clinical strains of Escherichia coli and Klebsiella pneumoniae were studied. MICs ranged from 0.0078 to 0.06 g/ml with standard inoculum tests. Ertapenem doses were administered once to five times daily to achieve various exposures, reported as the percentage of the dosing interval that the concentration of free ertapenem was in excess of the MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 10 publications
(7 reference statements)
0
20
0
Order By: Relevance
“…Animals were rendered neutropenic by the intraperitoneal administration of two doses of cyclophosphamide (Aventis, Paris, France) [6]; the first dose of 150 mg/kg at 96 h and the second dose of 100 mg/kg 48 h prior the experiment. The adequacy of the dose regimen for the induction of neutropenia was assessed in four rats by blood sampling 48 h after the second dose.…”
Section: Methodsmentioning
confidence: 99%
“…Animals were rendered neutropenic by the intraperitoneal administration of two doses of cyclophosphamide (Aventis, Paris, France) [6]; the first dose of 150 mg/kg at 96 h and the second dose of 100 mg/kg 48 h prior the experiment. The adequacy of the dose regimen for the induction of neutropenia was assessed in four rats by blood sampling 48 h after the second dose.…”
Section: Methodsmentioning
confidence: 99%
“…For carbapenems, the breakpoint that correlates best with bacteriostasis is an fTϾMIC of 20%, where maximal bactericidal activity is Ն40% (8, 22, 31, 31a). Recent animal work has demonstrated that no alternative pharmacodynamic breakpoints are needed to ensure efficacy against ESBL-producing isolates (1,19). In other words, even if the MICs increase for ESBL-producing isolates, as long as the antimicrobial regimen is able to exceed the critical fTϾMIC, efficacy remains.…”
Section: Discussionmentioning
confidence: 99%
“…The achievement of adequate fTϾMICs of 30 to 45% for meropenem and 20 to 30% for ertapenem, respectively, is the most likely explanation for these findings. Alternatively, since the raised MICs at a higher inoculum have been described as an artifact of in vitro susceptibility testing, they may not be clinically relevant (4,19,20).…”
Section: Discussionmentioning
confidence: 99%
“…(1, 15, 17, 19), but also depends on the bacterial strain being tested (13). The TϾMIC for bactericidal effects are larger; a TϾMIC of 30 to 55% is required for a 2-log-unit reduction in viable bacterial counts (15,17), and the maximum effect for some strains may require a TϾMIC of Ͼ60% (14,15). The relationships between carbapenem TϾMICs and antibacterial effect are less clear for S. aureus, including MRSA strains.…”
Section: Discussionmentioning
confidence: 99%